The Development of a Mathematics Learning Module on Proportion Material Based on STEM with Islamic Integration for Junior High School - Kristanti, Miya; Masamah, Ulfa (Universitas Islam Negeri Sunan Kudus, 2022)
21st-century learning requires a special approach which improve students’ learning outcomes, namely aspects of cognitive, affective, and psychomotor. Mathematics learning tools must still pay attention to the universal values of Islamic teachings and the use of technology, including STEM. The learning module is the teaching material used by teachers in the mathematics learning process. This study aims to develop and determine the level of validity of ISTEM-based mathematics learning modules on proportion material. This research was carried out at junior high school based on research and development with the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments were observation sheets, questionnaires, and interviews. The module has been validated by design experts and material experts. The results showed that the development of the module based on the assessment of material experts obtained an average percentage of 90.42% with appropriate criteria, learning expert assessments obtained an average percentage of 81.67% with appropriate criteria, and design expert assessments obtained an average percentage of 81.08%. The results of using the module obtained an average score of 85.71% with a total of 24 students who completed it. The module obtained very high assessment criteria and met the requirements for effective use in improving mathematical learning outcomes and was suitable for use in the mathematics learning process on proportion material for junior high school level. Thus, based on the results of this study, it is necessary to integrate ISTEM in the development of mathematics learning modules for junior high school on proportion materials. Pembelajaran abad ke-21 membutuhkan pendekatan khusus yang meningkatkan hasil belajar siswa, yaitu aspek kognitif, afektif dan psikomotorik. Perangkat pembelajaran matematika harus tetap memperhatikan nilai-nilai universal ajaran Islam dan pemanfaatan teknologi, diantaranya adalah STEM. Modul pembelajaran merupakan bahan ajar yang digunakan oleh guru dalam proses pembelajaran matematika. Penelitian ini bertujuan untuk mengembangkan dan mengetahui tingkat validitas modul pembelajaran matematika berbasis ISTEM pada materi perbandingan. Penelitian ini dilaksanakan di SMP berdasarkan penelitian dan pengembangan dengan model ADDIE yaitu Analysis, Design, Development, Implementation, Evaluation. Instrumennya adalah lembar observasi, angket dan wawancara. Modul tersebut telah divalidasi oleh ahli desain dan ahli materi. Hasil penelitian menunjukkan bahwa pengembangan modul tersebut berdasarkan penilaian ahli materi diperoleh persentase rata-rata 90,42% dengan kriteria sesuai, penilaian ahli pembelajaran memperoleh persentase rata-rata 81,67% dengan kriteria sesuai, penilaian ahli desain diperoleh rata-rata persentase 81,08%. Hasil penggunaan modul tersebut diperoleh nilai rata-rata 85,71% dengan total 24 siswa yang tuntas. Modul tersebut memperoleh kriteria penilaian sangat tinggi dan memenuhi syarat efektif digunakan dalam meningkatkan hasil belajar matematika dan layak digunakan dalam proses pembelajaran matematika materi perbandingan tingkat SMP. Dengan demikian, berdasar pada hasil penelitian tersebut, perlu ada integrasi ISTEM dalam pengembangan modul pembelajaran matematika materi perbandingan jenjang sekolah menengah pertama.